(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The thermal behavior of two polymorphic forms of rifampicin was studied by DSC and TG/DTG. The thermoanalytical results clearly showed the differences between the two crystalline forms. Polymorph I was the most thermally stable form, the DSC curve showed no fusion for this species and the thermal decomposition process occurred around 245 ºC. The DSC curve of polymorph II showed two consecutive events, an endothermic event (Tpeak = 193.9 ºC) and one exothermic event (Tpeak = 209.4 ºC), due to a melting process followed by recrystallization, which was attributed to the conversion of form II to form I. Isothermal and non-isothermal thermogravimetric methods were used to determine the kinetic parameters of the thermal decomposition process. For non-isothermal experiments, the activation energy (Ea) was derived from the plot of Log β vs 1/T, yielding values for polymorph form I and II of 154 and 123 kJ mol-1, respectively. In the isothermal experiments, the Ea was obtained from the plot of lnt vs 1/T at a constant conversion level. The mean values found for form I and form II were 137 and 144 kJ mol-1, respectively.